APPLICATION OF TECHNICAL AND VOCATIONAL EDUCATION TRAINING (TVET) IN THE LEARNING PROCESS OF PROGRAMMING LANGUAGE USING ONLINE COMPILER - Marwa Halim; Wijaya, Robby (STMIK TIME, 2023)
Advances in digital technology have influenced the transformation and growth of Technical and Vocational Education Training (TVET) globally. [1] The use of technology in the learning and training process for an educational institution has become a significant necessity in the competitive era of globalization. Many studies discussing the utilization of elearning in the teaching and learning process noted various challenges in the implementation in Indonesia. In this study the author wants to review the monitoring of the use of web-based compiler applications in the learning process of programming languages. The variables that will be used to measure the success of onlineGDB application utilization in the teaching and learning process include: The use of the GDB Online application, student understanding of programming languages, the final results in the learning process. The target respondents who were successfully collected were 146 people consisting of 141 students and 5 lecturers from various universities in North Sumatra-Indonesia. Data was collected by distributing questionnaires, observations and interviews. The results of this study indicate the use of the onlineGDB compiler application can improve the understanding of students in learning programming languages, this can be seen from the results of the compilation of questionnaires conducted for 3 months with 3 variables to measure the success of the programming language learning process, namely 1. The use of the GDB Online application, 2. Student understanding of programming languages, 3. The final results in the learning process.